MODEL PEMATAAN SOSIAL EKONOMI DAN TANTANGAN KESEJAHTERAAN NELAYAN KECIL DI KABUPATEN SERUYAN - Darmono Darmono; Sri Herlina; Sunan Triyadin (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
Seruyan Regency has significant fisheries potential, with a total production of 21,521.67 tons in 2022. However, this potential has not yet fully improved the welfare of small-scale fishers. This study aims to identify the socio-economic conditions of small fishers in Seruyan Regency, analyze the challenges they face, and develop a socio-economic mapping model that comprehensively represents their level of welfare. The research employs a qualitative method with a descriptive-analytical approach, using both primary and secondary data collected from small fishers, village officials, local government, and other related stakeholders. The findings reveal that small fishers in Seruyan Regency face major issues such as limited market access, low financial literacy, traditional fishing technology, and restricted access to capital and institutional support. Social factors such as low educational levels and limited adaptive capacity to change further worsen their situation. The socio-economic mapping model developed in this study is expected to serve as a foundation for local governments in formulating empowerment policies and programs that are more targeted, equitable, and sustainable